Once there was a house and you can make it! - Hindley, Judy (New York : Random House, 1986)
A small story of children playing imaginatively with cartons and other household materials used as houses, furniture, gas station, and tools is accompanied by the directions for making these things.
Keywords: Play-Fiction; Handicraft